New Diagnostic and Therapeutic Approaches for the Care of the Severely Injured Patient - Hildebrand, Frank; Horst, Klemens (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Trauma represents a leading cause of death, particularly in the younger population. Traumatic brain injury and hemorrhage are the most common causes of early death, whereas complications such as infections, (multi-)organ failure and "persistent inflammation, immunosuppression, and catabolism syndrome" (PICS) represent relevant factors for late adverse outcomes. Pre- and intra-hospital diagnostic and therapeutic standard operating procedures have been shown to beneficially influence posttraumatic outcome. However, development of patient-specific diagnostic and therapeutic strategies remains challenging due to uncertainties regarding the assessment of the individual risk profile. Furthermore, the relevance of prevention and rehabilitation measures to avoid unfavorable long-term consequences of trauma is not fully elucidated. With this Special Issue, we wanted to reflect the current knowledge about the pathomechanisms associated with the impact of severe injury and its consequences for the further clinical course on the one hand, and to point out new insights in regard to diagnostic and therapeutic approaches on the other hand. Furthermore, interesting aspects for future directions for the care of severely injured patients are illustrated.